2011
DOI: 10.1111/j.1365-2435.2011.01887.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of eggshell structure during rapid range expansion in a passerine bird

Abstract: Summary1. Environmental factors such as temperature, humidity and partial oxygen pressure can affect avian eggshell structure because gas exchange across the shell must allow sufficient water loss while preventing dehydration of the embryo. Studies of species with known chronology of colonization of novel environments provide a powerful insight into the relative importance of ecological factors shaping the evolution of eggshell structure. 2. Here, we examined changes in eggshell structure that accompanied rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…This foraging flexibility of Great Tits could possibly be the reason why we found that environmental conditions had no significant effect on eggshell thickness. Our results are in concordance with previous findings, as eggshell thickness also did not vary with laying date and ambient temperature in other bird species (Eeva and Lehikoinen 1995;Massaro and Davis 2004;Hargitai et al 2011;Stein and Badyaev 2011).…”
Section: Breeding Density (Pair/100 M Radius Circle)supporting
confidence: 95%
“…This foraging flexibility of Great Tits could possibly be the reason why we found that environmental conditions had no significant effect on eggshell thickness. Our results are in concordance with previous findings, as eggshell thickness also did not vary with laying date and ambient temperature in other bird species (Eeva and Lehikoinen 1995;Massaro and Davis 2004;Hargitai et al 2011;Stein and Badyaev 2011).…”
Section: Breeding Density (Pair/100 M Radius Circle)supporting
confidence: 95%
“…Hence, the rate of egg water loss during laying and incubation might not be determined by ambient temperature in these populations, but most likely by the female's behaviour (Higham and Gosler 2006). Further studies are needed to determine whether the relationship between shell thickness and temperature is due to immediate environmental constraints (as found in previous poultry studies; Hempleman et al 1993) or to adaptive evolution of shell structure (as suggested by Stein and Badyaev 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Likewise, less porous shells should be adaptive in these environments (Davis et al 1984, Davis andAckerman 1985). Previous findings in wild birds show either a positive effect of temperature on shell mass (Ojanen 1983) and thickness (Arad et al 1988) or no effect at all (Stein and Badyaev 2011). Bourgault et al (2007) found that blue tits Cyanistes caeruleus laid eggs with heavier shells in a colder deciduous forest compared with a coniferous forest; yet, the effects of temperature and habitat type could not be disentangled.…”
mentioning
confidence: 96%
“…Ricklefs and Smeraski (1983) cross-fostered eggs among nests of the European Starling ( Sturnus vulgaris ) shortly after laying, and found that the length of the incubation period depended on the incubation behavior of the foster parents, and also on the nest from which the eggs originated. They found that differences in incubation periods were associated with variation in the composition of eggs laid by both the original and foster mothers, as revealed by both nest-of-origin and nest-of-rearing effects, leading them to suggest that the formation of eggs may be correlated with maternal incubation behavior (see also Stein and Badyaev 2011). …”
Section: Introductionmentioning
confidence: 99%